2020
DOI: 10.1186/s12974-020-01886-2
|View full text |Cite
|
Sign up to set email alerts
|

Histamine 2/3 receptor agonists alleviate perioperative neurocognitive disorders by inhibiting microglia activation through the PI3K/AKT/FoxO1 pathway in aged rats

Abstract: Background Microglia, the principal sentinel immune cells of the central nervous system (CNS), play an extensively vital role in neuroinflammation and perioperative neurocognitive disorders (PND). Histamine, a potent mediator of inflammation, can both promote and prevent microglia-related neuroinflammation by activating different histamine receptors. Rat microglia express four histamine receptors (H1R, H2R, H3R, and H4R), among which the histamine 1 and 4 receptors can promote microglia activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 63 publications
3
8
2
Order By: Relevance
“…the release of the anti-inflammatory cytokine interleukin-10 (IL-10). This is further supported by both Chen et al (2020) who found that H 2 and H 3 receptor agonism inhibited laparotomyor LPS-induced microglial activation, pro-inflammatory cytokine production and cognitive decline and by Fang et al (2020) whereby H 4 receptor antagonism reduced microglial activation and TNF-α release in a rat model of Parkinson's disease. Along with histamine's ability to induce microglial activation and the subsequent release of both anti-and pro-inflammatory factors, it can also promote phagocytosis via H 1 receptor activation and the production of reactive oxygen species (Rocha et al, 2016) and prostaglandin E2 (Lenz et al, 2018).…”
Section: Histamine's Regulation Of Microgliasupporting
confidence: 56%
“…the release of the anti-inflammatory cytokine interleukin-10 (IL-10). This is further supported by both Chen et al (2020) who found that H 2 and H 3 receptor agonism inhibited laparotomyor LPS-induced microglial activation, pro-inflammatory cytokine production and cognitive decline and by Fang et al (2020) whereby H 4 receptor antagonism reduced microglial activation and TNF-α release in a rat model of Parkinson's disease. Along with histamine's ability to induce microglial activation and the subsequent release of both anti-and pro-inflammatory factors, it can also promote phagocytosis via H 1 receptor activation and the production of reactive oxygen species (Rocha et al, 2016) and prostaglandin E2 (Lenz et al, 2018).…”
Section: Histamine's Regulation Of Microgliasupporting
confidence: 56%
“…Emerging emphasis has been put on the role of neuroinflammation in the progression of PND 24,25 . Characterized by producing inflammatory mediators that facilitate the development and severity of PND, microglia play a crucial role in the progression of PND 26,27 . In a mouse model of PND, we investigate the correlation between galectin‐1 treatment and neurocognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in microglial signature induced by peripheral inflammation can translate into alterations in neuronal and synaptic functions. For instance, postoperative cognitive dysfunction is associated with microglia-induced neuroinflammation triggered by operation-induced peripheral inflammation [ 105 , 106 , 107 ]. TNF, IL-6 and IL-1β generated by microglia can profoundly affect synaptic transmission and plasticity and underlie cognitive and behavioral alterations occurring in peripheral inflammatory disease [ 108 , 109 , 110 , 111 , 112 ].…”
Section: Microglia Are Under the Influence Of Peripheral Inflammationmentioning
confidence: 99%